PANDEMIC EFFECTS AT PHYSICAL AND PSYCHOSOCIAL LEVEL OF THE ATHLETES - Dan-Mihai ROHOZNEANU; Florin Valentin LEUCIUC; Adrian GEORGESCU (Cluj University Press, 2023)
The pandemic COVID-19 has globally affected the physical activity behavior, forcing many people to isolate themselves for a long period of time. These actions caused and increased sedentary behaviors such as excessive sitting or using mobile devices. The lockdown and sedentary behavior have affected the health status and decreased the physical fitness, weakening one's body and inducing a low immunological response. The aim of the study was to determine how elite handball players were affected at physical and mental during the restrictions imposed by the spreading of the SARS - CoV - 2 virus. A questionnaire-based survey was used to conduct the study. For the questionnaire design we used Likert style with three or five level items. The participants voluntarily consented to anonymously participate in our study before completing the questionnaire. The participants were informed that the data would be used only for scientific purpose. The results of our study suggest that pandemic negatively influenced the sport preparation of the handball players due the fact that subjects trained themselves for a period of over 2 months and that meant a reduction of the physical activity (influencing the physical fitness level) to half comparing to a collective preparation for competition. At mental level more than 2/3 felt an increased level of anxiety due to the pandemic, the way that their life was changed and worries concerning their personal and professional future. This period of incertitude had a negative impact at mental level confirming our hypothesis. REZUMAT. Efecte pandemice la nivel fizic și psihosocial ale sportivilor. Pandemia COVID-19 a afectat la nivel global activitatea fizică, forțând mulți oameni să se izoleze pentru o perioadă lungă de timp. Aceste acțiuni au cauzat și au amplificat comportamentele sedentare, cum ar fi lipsa de activitate sportivă sau utilizarea dispozitivelor mobile. Restricționarea ieșirii din case și comportamentul sedentar au afectat starea de sănătate și au scăzut condiția fizică, slăbind organismul și inducând un răspuns imunologic scăzut. Scopul studiului a fost de a determina modul în care jucătorii de handbal de elită au fost afectați fizic și psihic în timpul restricțiilor impuse de răspândirea virusului SARS - CoV - 2. Pentru realizarea studiului folosit metoda anchetei pe bază de chestionar. Pentru proiectarea chestionarului am folosit scala Likert cu trei sau cinci itemi de nivel. Participanții au consimțit voluntar să participe în mod anonim la studiul nostru înainte de a completa chestionarul. Participanții au fost informați că datele vor fi utilizate numai în scop științific. Rezultatele studiului nostru sugerează că pandemia a influențat negativ pregătirea sportivă a jucătorilor de handbal din cauza faptului că subiecții s-au antrenat singuri pentru o perioadă de peste 2 luni și asta a însemnat o reducere a activității fizice (influențând nivelul de fitness) la jumătate comparativ cu pregătirea colectivă pentru competiție. La nivel mental, mai mult de 2/3 au simțit un nivel crescut de anxietate din cauza pandemiei, a modului în care le-a fost schimbată viața și a îngrijorărilor cu privire la viitorul lor personal și profesional. Această perioadă de incertitudine a avut un impact negativ la nivel mental confirmând ipoteza noastră. Cuvinte cheie: pandemie, antrenament, handbal, comunicare, echipă Received 2022 November 09; Revised 2023 January 21; Accepted 2023 January 24; Available online 2023 May 30; Available print 2023 June 30.